RNA aptamer probes as optical imaging agents for the detection of amyloid plaques. - Christian T Farrar; Christopher M William; Eloise Hudry; Tadafumi Hashimoto; Bradley T Hyman (PLoS ONE)
Optical imaging using multiphoton microscopy and whole body near infrared imaging has become a routine part of biomedical research. However, optical imaging methods rely on the availability of either small molecule reporters or genetically encoded fluorescent proteins, which are challenging and time consuming to develop. While directly labeled antibodies can also be used as imaging agents, antibodies are species specific, can typically not be tagged with multiple fluorescent reporters without interfering with target binding, and are bioactive, almost always eliciting a biological response and thereby influencing the process that is being studied. We examined the possibility of developing highly specific and sensitive optical imaging agents using aptamer technology. We developed a fluorescently tagged anti-Aβ RNA aptamer, β55, which binds amyloid plaques in both ex vivo human Alzheimer's disease brain tissue and in vivo APP/PS1 transgenic mice. Diffuse β55 positive halos, attributed to oligomeric Aβ, were observed surrounding the methoxy-XO4 positive plaque cores. Dot blots of synthetic Aβ aggregates provide further evidence that β55 binds both fibrillar and non-fibrillar Aβ. The high binding affinity, the ease of probe development, and the ability to incorporate multiple and multimodal imaging reporters suggest that RNA aptamers may have complementary and perhaps advantageous properties compared to conventional optical imaging probes and reporters.